House Prices, Household Debt and Monetary Policy. - Nickell, S (2003)
In this speech, Stephen Nickell, a member of the Bank's Monetary Policy Committee, addresses the question: should we keep interest rates higher than would be required to hit the inflation target during 2004 in order not to encourage further debt accumulation and increases in house prices? He argues that the right answer to the question is no.